Partnerships in health research: Experiences from a developing country - Banjara, MR (Kathmandu University Medical Journal, 2009)
doi: 10.3126/kumj.v7i1.1755     Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 2-3